If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(m + -1) = 0 Reorder the terms: 2(-1 + m) = 0 (-1 * 2 + m * 2) = 0 (-2 + 2m) = 0 Solving -2 + 2m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2m = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 2m = 0 + 2 2m = 0 + 2 Combine like terms: 0 + 2 = 2 2m = 2 Divide each side by '2'. m = 1 Simplifying m = 1
| 1+4x+4=-11 | | 37c+6-34c=33 | | 4h+5-(7h-8)= | | 125=p+34 | | -3x^5+9x^4-15x=0 | | -6(4x-1)+5(5x-2)-4=2-8 | | 1+(2x-1)=5x-(20-x) | | 71t-62t+3=-31t | | 4=4b-5-3 | | 5(-3+3p)= | | -8x-11x=-152 | | 15(4r+15)= | | 3a^2+23a+40=0 | | 11x-(3x-11)=7+7x | | 2x+5=2-(x-9) | | c-7=21.95 | | 6+0.2r=-6 | | 3z^2+12z+13=0 | | 2k+6k=8 | | y-6-7(y-5)+5(6y+1)=y-6-7xy-5-5+5(6y+1) | | 7.5x=270 | | 3*42-(7+3)/2+5= | | 2(3ax-2y)-6ax=-3(ax+2y) | | 40=10-2y | | 7m=3m+4 | | 4(1+4n)= | | -4n+2+2n=-3(2n+2) | | 12(6y-4)= | | 0.8t-5=7 | | y=c+u-x | | 4x^2+17x=-18 | | y^2-8y=-13 |